30- day mortality following trauma and orthopaedic surgery during the peak of the COVID-19 pandemic: A multicentre regional analysis of 484 patients. (June 2020) - Karayiannis, P. N.; Roberts, V.; Cassidy, R.; Mayne, A. I. W.; McAuley, D.; Milligan, D. J.; Diamond, O.
No abstract available